Burden of corticosteroid therapy in patients with immunoglobulin A nephropathy (IgAN): a systematic literature review - Sarah N. Ali; Nicole Fusco; Dilip Makhija; Vakaramoko Diaby; Tosin Oladapo; Darsh Devani; Cibele Pinto; Mohit Mathur; Ancilla W. Fernandes (BMC Nephrology)
Abstract Background Immunoglobulin A nephropathy (IgAN) is one of the most common forms of primary glomerulonephritis (GN) worldwide. While specific treatment differs regionally, treatment usually focuses on background therapy, with short-term (≤ 6 months) corticosteroids recommended as an add-on treatment for patients at high risk of progressive chronic kidney disease. Although corticosteroids can help to manage IgAN, treatment with corticosteroids may lead to undesirable adverse outcomes. Objective To highlight corticosteroid treatment burden in patients with IgAN globally. Methods Embase, MEDLINE, and Cochrane CENTRAL were searched for articles published in any language from January 1, 2013 to August 24, 2023. Eligible studies reported ≥ 1 outcome related to the clinical, humanistic, or economic burden of corticosteroids in patients with IgAN. Articles were independently screened by 2 reviewers. Data extraction and quality assessment were completed by 1 researcher and validated by a second. Results are reported among the number of studies with data on each outcome. Results Of 1,024 records screened, 64 studies were included. Of 37 studies reporting treatment duration, 68% found that corticosteroids were used long-term (range: 8–24 months). In studies reporting data for long-term use (> 6 months), there were more overall AEs and serious AEs with corticosteroids than with comparator treatments (e.g., background therapy alone, tonsillectomy, placebo). Rates of metabolic AEs, Cushing’s syndrome, edema and sleep disorders were also higher with long-term corticosteroids than with comparator treatments; however, most studies did not report the statistical significance of these results. Infection rates were similar between corticosteroids and comparator treatments. Conclusions Current guidelines recommend short-term corticosteroid treatment for patients at high risk of progression but long-term use appears to be widespread. Corticosteroids may lead to adverse outcomes and should therefore be reserved only for IgAN patients most at risk of rapid progression to end-stage kidney disease and for limited duration. Novel corticosteroid-sparing therapies are necessary to supplement the current treatment landscape.